HLA-DQ B1*0201 and A1*0102 Alleles Are Not Responsible for Antituberculosis Drug-Induced Hepatotoxicity Risk in Spanish Population - Leiro-Fernández, Virginia; Valverde, Diana; Vázquez-Gallardo, Rafael; Constenla-Caramés, Lucía; del Campo-Pérez, Víctor; Fernández-Villar, Alberto (Frontiers in Medicine, 2016)
Aims: To evaluate the role of HLA class II DQB1*0201 and DQA1*0102 in the risk of antituberculosis drug-induced hepatotoxicity in a cohort of tuberculosis patients of Caucasian origin from Spain. Methods: Matched case-control study including active tuberculosis (TB) patients from Spain (Caucasian) treated with first line antituberculosis drugs (ATD) (Isoniazid, Rifampin and Pyrazinamide). Presence or absence HLA class II DQB1*0201 and DQA1*0102 alleles were compared between cases and controls. Results: We included 110 TB patients, 55 antituberculosis drug-induced hepatotoxicity (ATDH) cases and 55 sex-matched controls. The analysis of the presence of HLADQB1*0201 and HLADQA*0102, did not show significative differences between both groups [presence of HLADQB1*0201 53.6% of cases vs 45.4% of controls, OR: 1.63 95% CI (0.62-4.52) p= 0.38; presence of HLADQA*0102 7.5% of cases vs 20% of controls OR: 0.36 95%CI (0.08-1.23, p=0.12)]. After multivariate logistic regression analysis including in the model other potential risk factors of hepatotoxicity HLA class II DQB1*0201 and DQA1*0102 alleles were not found significantly associated with the risk of development ATD-induced hepatotoxicty. Results: We could not demonstrate an association between HLADQA1*0102 and HLADQB1*0201 with the risk of ATDH in this Caucasian population of Spanish origin.